Ruiz, Pablo M., Four Cold Chapters on the Possibility of Literature: Leading Mostly to Borges and Oulipo, Champaign, Dalkey Archive Press, 2014, 382 pp. - Torbidoni, Juan (2020)
Fil: Torbidoni, Juan. Pontificia Universidad Católica Argentina; Argentina